Study on reservoir characteristics, pore-throat structure, and origin of tight oolitic reservoirs: A case study of Triassic Feixianguan Formation, NE Sichuan Basin, SW China - Ren, Guanxiong; Qin, Qirong; Zhang, Qiang; Guo, Yanbo; Ye, Zhaoyang (Frontiers in Earth Science, 2023)
Origin and pore-throat structure of different lithofacies are key issues in exploration and development of tight oolitic reservoirs. Based on core and thin section observation, four types of lithofacies can be recognized in the Feixianguan Formation oolitic reservoir: (1) oolitic limestone with intergranular pores (Lithofacies A), (2) oolitic limestone with mold pores (Lithofacies B), (3) oolitic dolostone (Lithofacies C) and (4) silty crystalline dolomite and fine crystalline dolostone (Lithofacies D). The subsurface core samples from the different lithofacies were studied using mercury injection, 3-D CT scanning and nuclear magnetic resonance, indicating that Lithofacies D possesses the best pore-throat structure and reservoir connectivity. The pore-throat structure of Lithofacies C is very similar to that of D, but the heterogeneity is much stronger. By comparison, the pore-throat structure of Lithofacies A and B are relatively poor. Although the pore heterogeneity of Lithofacies B is weaker than that of Lithofacies A, there is no effective throat connection in Lithofacies B. On the basis of oolitic shoal deposition, the factors controlling the origin of different lithofacies are meteoric freshwater leaching and then dolomitization. Meteoric freshwater leaching dominates the origin of Lithofacies B, but does not affect the origin of Lithofacies C. Lithofacies C is jointly controlled by seepage-reflux and hydrothermal dolomitization fluids. The origin of Lithofacies D is only controlled by seepage-reflux dolomitization. Some other diagenesis may also have impacts on petrophysical properties of different lithofacies, but they does not play a decisive role in the origin of different lithofacies.